Destinazione Jihad I foreign fighters d'Italia - Vidino, Lorenzo; Marone, Francesco (Ledizioni, 2018)
In recent years, thousands of foreign fighters have left over 100 countries to join armed groups, especially jihadist groups, in Syria and Iraq and in other theaters of war. The phenomenon has also affected Italy, although to a much lesser extent than in other European countries. The foreign fighters of Italy are, in fact, about 130. What are the socio-demographic characteristics of these individuals? Where did they live before they left? Were they part of extremist networks in Italy and in Europe? What role did they play in the conflict area? How many have already returned? Are there common profiles? These are just some of the questions that this ISPI Report tries to answer. Through a detailed analysis of the profiles of foreign fighters linked to Italy, on the basis of original data, the peculiarities of the entire national contingent are highlighted for the first time, also thanks to the comparison with other Western countries.
Description based on print version record.
KU Open Services
Keywords: Political Science / Public Policy / Military Policy; Social Science / Regional Studies; Political science; Electronic books